Subtenon triamcinolone injection to treat serous choroidal detachment after glaucoma surgery: A case series. Issue 1 (January 2023) - Nilforushan, Naveed; Abolfathzadeh, Navid; Najafzadeh, Farhad; Samimifar, Deniz
Purpose: To report the effect of subtenon triamcinolone acetonide (TA) injection in the treatment of serous choroidal detachment (SCD) after glaucoma surgery. Methods: In this prospective case series, patients with persistent, non-resolving, or progressive SCD after glaucoma surgery were enrolled. For those with non-resolving or progressive SCD despite of using systemic corticosteroids, topical atropine and topical steroids, one milliliter of TA (40mg/mL) was injected inferotemporally into the posterior subtenon space. Results: Sixteen consecutive patients with a mean ± SD age of 70.12 ± 11.12 years were included in this study. After injection of subtenon TA, SCD was completely resolved after 1 to 4 weeks, with deepening of the anterior chamber in all cases. All cases were followed for at least 6 months after the injection with no signs of recurrence. Conclusion: Subtenon injection of TA is a safe and effective modality of treatment for resolving a persistent or progressive SCD after glaucoma surgeries.